Art Education Resiliency: Co-generatively in a Community of Practice - Patterson, Pam; Romanov, Roman; Hawthorn, Matt (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2024)
Art/Design Education Resiliency: Co-generatively in a Community of Practice is a co-authored dialogic/dialectic conversation among co-founders of the Creative Research Inclusive Practices (CRIP) Lab located at OCAD University. Founders are Pam Patterson, Faculty of Art, and School of Graduate Studies, OCAD U; Roman Romanov, Faculty of Design, OCAD U; and Matt Hawthorn, Head Design, University of Derby. The three have named their collective research practice as a form of snorkelling1! They swim the surface of discourse in play, deep diving into projects or exhibitions when paradoxical or multi-positional situations arise. It is a critical and yet deeply pleasurable discursive practice.